A Farm Typology for Adoption of Innovations in Potato Production in Southwestern Uganda - Priegnitz, Uta; Lommen, Willemien J. M.; Onakuse, Stephen; Struik, Paul C. (Frontiers in Sustainable Food Systems, 2019)
In Uganda, low productivity of potato might be associated with poor and diverse adoption of innovative crop management practices. This paper aims to identify the potato farm typologies in southwestern Uganda, i.e. collections of farms that are homogeneous in uptake of innovations (use of fertilizer, organic input, fungicides, pesticides, seed selection methods, seed refreshment by using quality declared seed, and sole cropping), and to analyse these typologies based on socio-economic characteristics, access to agricultural extension services, memberships of farmers’ groups, yield levels of potato and return rates. A farm household survey (n=270) was carried out and principal component analysis and cluster analysis were used to identify types of farms differing in adoption of innovations. Four farm types were identified that demonstrated significant differences in uptake of innovation practices; despite the small differences in yield among farm types, differences in uptake were associated with significant differences in the yield and further in land ownership, availability of labourers and cash, economical return, and access to knowledge. The farm type with high frequencies of using organic input, fungicide input, pesticide input, seed selection method, quality declared seed and sole cropping achieved highest potato productivity; the farm type with frequent use of fungicide input and use of seed plot technology or positive selection was associated with the lowest potato yield. The findings emphasise associations between innovation uptake and farm characteristics. Opportunities for improvement through extension services and shared knowledge can achieve wider adoption, enhance potato productivity and increase income for smallholder farmers.